NUMERICAL ANALYSIS OF HEMODYNAMIC FORCES THROUGH STENOTIC ARTERY (Journal of Mechanical Engineering, 2013)
A numerical analysis is carried out to demonstrate the variation of two hemodynamic forces: wallshear stress and pressure in the flow field of stenotic artery. The artery has 75% stenosis severity withaxisymmetric cosine shaped stenosis. The wall of the vessel is considered to be rigid. A sinusoidal pulsatile flowis assumed as inlet boundary condition. During the simulation both standard k-? model of low Reynoldscorrection and standard k-? model are used. Some analysis with standard k-? model with low Reynoldscorrection show better agreement with previous experimental results. The peak wall shear stress is found to belocated proximal to the stenosis throat. The results from the standard k-? turbulence model illustratesoscillating wall shear stress downstream the stenosis throat throughout the time period. The pressure gradientat the throat is highest at peak flow condition. These factors contribute to further growth and rupture ofplaques.DOI: http://dx.doi.org/10.3329/jme.v43i1.15780